Pengembangan Penuntun Praktikum Biologi Molekuler Dasar Berbasis Project-Based Learning untuk Meningkatkan Penguasaan Konsep dan Keterampilan Proses Sains Siswa SMK - Lestari, Sri Ratna; Sipahutar, Herbert; Harsono, Tri (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed to develop a Project-Based Learning (PjBL)-oriented practicum guide for basic molecular biology to enhance students’ concept mastery and science process skills in the IPAS subject, particularly on the topic of living organisms and their environment. The development model used was ADDIE (Analysis, Design, Development, Implementation, Evaluation). The research subjects were grade X students from the Health and Social Work Expertise Program at SMKS Galang Insan Mandiri Binjai. Data were collected through needs analysis questionnaires, expert validation sheets, student response questionnaires, and tests of cognitive understanding and science process skills. The practicum guide consisted of three core activities: simple DNA isolation, in silico PCR simulation, and basic electrophoresis, all designed in alignment with PjBL syntax. Expert validation results indicated a high level of feasibility: content expert (92.53%), instructional design expert (98.08%), and layout expert (94.81%). The guide’s effectiveness was evaluated through an independent sample t-test, showing significant differences between experimental and control groups in both concept mastery (t = 9.299; p = 0.000) and science process skills (t = 8.800; p = 0.000). These findings demonstrate the practicum guide's effectiveness in improving the quality of molecular biology instruction and fostering students’ ability to apply scientific processes in a contextual and collaborative manner. The study recommends adopting PjBL-based practicum guides as a relevant instructional strategy for vocational education in the 21st century.